2012
DOI: 10.2190/om.64.1.b
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Version of the Multidimensional Orientation toward Dying and Death Inventory (Moddi-F/Chin): An Introduction

Abstract: Preliminary data on the test criteria of the Chinese version of the Multidimensional Orientation Toward Dying and Death Inventory (MODDI-F/chin) are presented. Data from a sample of Hong Kong college students (N = 256) revealed internal consistencies of the eight subtests between .68 and .91, on the whole favorable shape of frequency distributions, and evidence of construct as well as differential validity of the instrument. The use of the full set of 47 items is recommended for the time being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…Examination of the goodness of fit indices indicated that the model had a good fit to the data. This finding is in line with those of previous studies examining the factor structures of the Chinese, Hong Kongese, and German versions of the inventory (Wittkowski, 1996;Wittkowski et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Examination of the goodness of fit indices indicated that the model had a good fit to the data. This finding is in line with those of previous studies examining the factor structures of the Chinese, Hong Kongese, and German versions of the inventory (Wittkowski, 1996;Wittkowski et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The positive correlations of fear and acceptance, as well as the negative relationship between the fear and acceptance dimensions, provided the theoretical data for the formation of scale and confirmed its construct validity (Wittkowski et al, 2012).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The Chinese version of MODDI‐F (MODDI‐F/chin) was validated in Hong Kong (Wittkowski et al . 2011–2012). Our study used this validated Chinese version.…”
Section: Methodsmentioning
confidence: 99%